Clinical evaluation of botulinum toxin A in the management of temporomandibular myofascial pain. Issue 2 (February 2020) - Stonehouse-Smith, Daniel; Begley, Anne; Dodd, Martin
Abstract: We did a clinical service evaluation of patient-reported outcomes for pain and change in interincisal distance in patients treated with botulinum toxin A (BTX-A) for temporomandibular myofascial pain at nurse-led clinics. We retrospectively reviewed the clinical records of 100 patients and the prescribing patterns of two OMFS consultants. The mean starting pain score of 7.54 out of 10 was reduced by a mean (SD) of 2.48 (2.1) points after the intervention (p < 0.001). The most common prescription was for 100 units (n = 59 prescriptions). The change in the mean pain scores did not differ significantly whether 100 or 200 units were prescribed (p = 0.19). Interincisal distance increased by a mean (SD) of 0.5 (5.24) mm after treatment with BTX-A, which was not significant (p = 0.35). In most cases the treatment helped to manage and reduce the symptoms of temporomandibular myofascial pain. Considerable improvement in interincisal distance as a result of this treatment alone, however, is unlikely, but it may have a role in a multifaceted approach, particularly when other conservative methods have failed. The use of a pro forma may allow for more consistent record keeping and the detailed assessment of patient-reported pain scores in the weeks and months after treatment. Development of an electronic patient-reported outcome (ePRO) tool may facilitate this further.